THE EFFECT OF STUDENTS SELF-EFFICACY LEVEL IN USING TECHNOLOGY ON PRE-SERVICE TEACHER TEACHING PERFORMANCE - Amalia, Fauzia Rahma; Widhiatama, Daniel Ari (Peneliti.net, 2023)
The widespread use of technology across all parts of life is finally forcing educators to integrate current technology into the classroom environment in response to the growing needs of millennial learners. One of the efforts to integrate technology into the classroom is through pre-service teachers' self-efficacy when using technology. Self-efficacy is the ability of a teacher to have the confidence to influence students in learning to achieve learning targets; in this study, especially using technological knowledge. This study gathered data on preservice teachers’ self-efficacy in using technology through questionnaire survey and observation. The partial least squares (PLS) of the structure equation modelling (SEM) technique used to analyze the data. This study involved students from PBI Universitas Mercu Buana Yogyakarta batch 2019 and 2020. The research was conducted by non-random sampling. This study uses quantitative methods of research. According to Creswell (1994), quantitative research explains phenomena by collecting numerical data analyzed using mathematically based methods (in particular, statistics). This study aimed to find out how preservice teachers' self-efficacy level regarding the use of technology in microteaching classes and the effect of students’ self-efficacy level in using technology on pre-service teachers' teaching performance. This study’s results show an effect between preservice teachers’ self-efficacy (X) on preservice teachers’ teaching performance. It can be seen from the parameter coefficient value is 0.334, meaning that for every one-unit increase in Self Efficacy, Teaching Performance will increase by 0.334 units. This study concluded that the research data was analyzed using the Partial-Least Squares Structural Equation Modeling. It concluded that there was a significant effect between the preservice teachers’ self-efficacy in using technology on pre-service teachers' teaching performance.